Kıdem tazminatı karşılığı hesaplamasında iş kanunu ile Türkiye muhasebe standartlarındaki düzenlemelerin karşılaştırılması - (:unkn) unknown (My University, 2011)
Bu çalısmanın amacı, kıdem tazminatı karsılıgının hem Is Kanunu hem de Türkiye Muhasebe Standartlarındaki düzenlemelere göre hesaplama ve muhasebelestirme esaslarını karsılastırmalı olarak ortaya koymaktır. Kıdem tazminatı, hizmet sözlesmesinin kanunda sayılan nedenlerden biri ile sona ermesi halinde isveren tarafından yapılan bir ödemedir. Kıdem tazminatı isletmeler için bir sorumluluk, çalısanlar açısından da bir hak olarak her iki tarafı da ilgilendiren bir konudur. Kıdem tazminatı, hizmet sözlesmesi sona erdiginde ve tazminata hak kazanıldıgında ödenecektir. Ancak gelecekte ortaya çıkabilecek bu ödeme için her hesap döneminde karsılık ayrılması ve finansal tablolarda raporlanması TMS-19 “Çalısanlara Saglanan Faydalar” standardında düzenlenmistir. Türk vergi mevzuatında ise böyle bir karsılık ayırma zorunlulugu bulunmamaktadır. 6102 sayılı Türk Ticaret Kanunu’nun yasalasması ile Türkiye Muhasebe Standartlarını uygulama, 1 Ocak 2013’den itibaren zorunlu hale geleceginden kıdem tazminatı karsılıgının hesaplanması ve muhasebelestirilmesi de zorunlu olarak uygulanacaktır. Konu üç ana bölümde ele alınarak incelenmis ve birinci bölümde kıdem tazminatının yasal düzenlemelerdeki yeri ve karsılık ayırma uygulaması hakkında bilgiler verilmistir. Ikinci bölümde kıdem tazminatı karsılıgının hesaplanması, Is Kanunu ve TMS-19 açısından ayrı ayrı incelenmis ve örneklerle açıklanmıstır. Üçüncü bölümde ise hesaplanan kıdem tazminatı karsılıgının muhasebelestirilmesi ele alınmıstır. Burada da yine vergi mevzuatı ile TMS-19’a göre muhasebelestirme karsılastırmalı olarak açıklanmıstır.

The objective of this study is to put forward the basis of the calculation and the accounting of termination indemnity provisions comparatively as to the arrangements in both the Turkish Labor Law and the Turkish Accounting Standards. Termination indemnity is a payment made in case of the termination of the employment contract from one of the reasons enumerated at the law. Termination indemnity is a subjects related to both parties as being a responsibility for corporations and a right from the point of employees. Termination indemnity shall be paid when the employment contract has ended and when the right to the indemnity is attained. However the provision of an allowance for this payment that may arise in the future and it being reported in the financial tables has been regulated in the standard TAS-19 “Advantages Granted to Employees”. In the Turkish Tax Legislation there is no such obligation to provide for such an allowance. With the enacting of the Turkish Trade Law No. 6102, as the implementation of the Turkish Accounting Standards will become mandatory as of January 1st, 2013; the calculation and the accounting of provision for termination indemnity will be implemented mandatorily. The subject has been examined by considering it in three main parts and in the first part information about the place of the termination indemnity in legal arrangements and the implementation of the provision has been presented. In the second part the calculation of the termination indemnity has been examined separately from the Labor Law and TAS-19 aspects and has been explained with samples. In the third part the accounting of the calculated termination indemnity has been considered. Accounting as to both the Turkish Tax Regulations and TAS-19 has been explained comparatively as well in here.
Keywords: İktisat; İşletme